Low-Voltage Electrical Installations : (IEC, 2011)
The particular requirements of this part of IEC 60364 apply to the selection and erection of extra-low-voltage lighting installations supplied from sources with a maximum rated voltage of 50 V a.c. or 120 V d.c.